2021
DOI: 10.1111/1744-9987.13738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of demographic and clinical risk factors for high interdialytic weight gain

Abstract: Xerostomia and hyposalivation are highly prevalent in hemodialysis (HD) patients and this is effective in increased fluid intake. The aim of this study is to determine the demographic and clinical risk factors associated with high interdialytic weight gain (IDWG) in nondiabetic HD patients. In total, 52 eligible HD patients were recruited in this cross‐sectional study. Patients were divided into two groups according to % IDWG: Group 1: High IDWG (≥3%) and Group 2: normal IDWG (<3%). Plasma osmolarity (POsm), u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…There are many causes of xerostomia in HD patients. It has been reported that the development of xerostomia among HD patients can cause oral and gingival diseases, interdialytic weight gain due to increased fluid consumption, anxiety, depression, and difficulty in compliance with fluid control [5, 6]. It also affects clinical parameters such as xerostomia, kt/V, and urea reduction ratio in dialysis patients [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many causes of xerostomia in HD patients. It has been reported that the development of xerostomia among HD patients can cause oral and gingival diseases, interdialytic weight gain due to increased fluid consumption, anxiety, depression, and difficulty in compliance with fluid control [5, 6]. It also affects clinical parameters such as xerostomia, kt/V, and urea reduction ratio in dialysis patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…All these factors reduce the quality of life. HD treatment causes a decrease in salivary flow rate and changes in salivary composition [6, 9, 10]. Therefore, it is very important to evaluate xerostomia in HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Penambahan IDWG dipengaruhi oleh beberapa faktor seperti ketidakpatuhan terhadap asupan cairan dan garam (19). Selain itu, berbagai faktor dapat mempengaruhi kenaikan IDWG, diantaranya intake cairan, rasa haus, dukungan sosial dan keluarga, self-efficacy, stres dan lama HD (20,28).…”
Section: Pembahasanunclassified